Quantitative Evaluation of Broadband Photoacoustic Spectroscopy in the Infrared with an Optical Parametric Oscillator - Henry Bruhns and Marcus Wolff and Yannick Saalberg and Klaus Michael Spohr (Sensors, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. We evaluate the spectral resolution and the detection thresholds achievable for a photoacoustic spectroscopy (PAS) system in the broadband infrared wavelength region 3270 nm ≲ λ ≲ 3530 nm driven by a continuous wave optical parametric oscillator (OPO) with P ≈ 1.26 W. The absorption spectra, IPAS (λi), for diluted propane, ethane and methane test gases at low concentrations (c ~ 100 ppm) were measured for ~1350 discrete wavelengths λi. The IPAS (λi) spectra were then compared to the high resolution cross section data, σFTIR, obtained by Fourier Transform Infrared Spectroscopy published in the HITRAN database. Deviations of 7.1(6)% for propane, 8.7(11)% for ethane and 15.0(14)% for methane with regard to the average uncertainty between IPAS (λi) and the expected reference values based on σFTIR were recorded. The characteristic absorption wavelengths λres can be resolved with an average resolution of δλres ~0.08 nm. Detection limits range between 7.1 ppb (ethane) to 13.6 ppb (methane). In an additional step, EUREQA, an artificial intelligence (AI) program, was successfully applied to deconvolute simulated PAS spectra of mixed gas samples at low limits of detection. The results justify a further development of PAS technology to support e.g., biomedical research.
Keywords: EUREQA; Gas sampling; PAS; OPO; Hydrocarbons; Optical-parametric oscillator; Photoacoustic spectroscopy; Spectral deconvolution